NICRIBUTANIC ACID - Abralova Nafisa (Journal of new century innovations, 2023)
- Hello, dad! Uh-uh-uh-uh... Did you light something in the room again? What did you invent this time? Your hair is also slightly burnt. - Y-y-yes. I am o-on a grand d-d-dis-c-covery. - What other discovery, dad? Look at me, I got a new dress today. You've been inventing something for twenty years? You're going to get sick. The "Yutarbon" you made a week ago swallowed the spoon and released a pie. He swallowed his fork and took out bread. "Giftak", which you made even earlier, is producing silver from the dresses at home. We won't have any clothes left to wear. Come up with such a fabric, let it follow your health. After all, soon your daughter will become a bride in another house. Then who will be kind to you? If you don't mind going with us... - M-maybe I'll figure it out, P-pink. (She liked to call her daughter that because she always wore a pink dress). It is a l-l-liquid a-c-cid called "N-n-nicributanic a-a-c-cid". - Dad, what kind of liquid? If you don't mind, I'll shave off your keeling hair. Your glasses are broken too. Give me the test tube in your hand. - B-b-be ca-r-reful. T-t-turns to st-t-tone. - Turns it into stone??? - Y-y-yeah-h Pink carefully held up the nicributanic acid in the test tube and peered at it. Then he dropped a drop on the cactus that was shining in the pot. The cactus turned to stone one minute, and the next it cracked and split into small pieces of rock. - Yeah, yeah, after all, I will turn a lot of unnecessary people into stones. My dad is a genius! We will also turn the community of scientists who despised us into stone, Dad. Believe me, it is enough to drop a drop from the head of the kalbosh. Just one drop. - N-n-no. D-don't do it, P-pinky! G-give m-me the a-c-c-cid! G-g-give! The father, who began to take Nicributanic acid, was not strong enough for his daughter. He touched her fingers and pulled her to him. The test tube fell to the ground. Only one drop of the acid managed to touch Professor Ilmiy. A minute later, the professor turned to stone. And Pink was crying, hugging her father's legs, who had turned to stone. "I'm sorry," she cried. A minute later, all that was left of his father were small pieces of stone. Daaaaaaaaaaaaaaaaaad! "Giftak" began Pinky’s new shirt...